2008
DOI: 10.1080/13880200802367189
|View full text |Cite
|
Sign up to set email alerts
|

Antiurolithiatic Property ofMoringa oleiferaRoot Bark

Abstract: In spite of tremendous advances in the field of medicine, there is no truly satisfactory drug for the treatment of renal calculi. In the present study, the efficacy of the root bark of Moringa oleifera Lam. (Moringaceae) as an antiurolithiatic agent was investigated using an experimentally induced urolithiatic rat model. Hyperoxaluria was induced in rats using 0.75% ethylene glycol in water. Aqueous (AqE) (200 mg kg −1 body weight) and alcoholic extracts (AlcE) (200 mg kg −1 body weight) of the root bark of M.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
19
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 17 publications
0
19
0
Order By: Relevance
“…It has been reported that oxalate plays an important role in stone formation and have about 15-fold greater effect than urinary calcium. The changes in the urinary oxalate level are relatively much more important than those of calcium [24] . Elevated urinary calcium is a favouring factor for nucleation of calcium oxalate from urine and further crystal growth [31] .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been reported that oxalate plays an important role in stone formation and have about 15-fold greater effect than urinary calcium. The changes in the urinary oxalate level are relatively much more important than those of calcium [24] . Elevated urinary calcium is a favouring factor for nucleation of calcium oxalate from urine and further crystal growth [31] .…”
Section: Discussionmentioning
confidence: 99%
“…Due to this, the waste products, particularly nitrogenous substances such as urea, creatinine, BUN and uric acid get accumulated in blood [24] . In calculi-induced rats, marked renal damage was seen as indicated by the elevated serum levels of creatinine, urea, BUN and uric acid, which are markers of glomerular and tubular damage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The plant is native to northern India where it was noted as medicinal plant around 2000 BC. The pods and leaves are rich in protein and minerals and cooked as vegetable (Verma et al, 1976), posses certain bioactivities such as antiurolithiatic (Karadi et al, 2008), anti-infl ammatory (Sulaiman et al, 2008), antiasthmatic (Agrawal & Mehta, 2008), antioxidant and hepatoprotective (Fakurazi et al, 2008) have been reported. In literature, the presence of trigonelline was not previously recorded in M. oleifera.…”
mentioning
confidence: 99%